Drill Method to Improve Students' Prayer Movements - Ridha Nurjannah; Imam Tabroni; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2023)
Background. The drill method is one form of method used in activity-based learning that can train motoric or movement in students. Purpose. In this study, researchers used the Classroom Action Research method (action research) using the design of Kemmis and Taggart in the form of a spiral cycle which includes the design stages; first planning (planning), second action (acting). Method. third observation (observation), fourth reflection (reflection). Based on the results of class action, the prayer movements of MDA students. Al-Idrus experienced an 80% improvement from the pre-action results. Results. In cycle I meeting I there were 8 students categorized as skilled (80%), 2 students categorized as starting to be skilled (20%). Conclusion. And cycle II meeting II there were 8 learners categorized as very skilled (80%), 2 learners categorized as skilled (20%)